Clinical outcomes of early closure versus conservative strategy after diagnosis with atrial septal defect: a nationwide population-based cohort study. (9th February 2022) - Min, Sun-Yang; Lee, Ji Sung; Park, Duk-Woo; Song, Jong-Min
Abstract: OBJECTIVES: The long-term clinical benefits of atrial septal defect (ASD) closure remain controversial. We aimed to compare long-term clinical outcomes between patients who underwent early surgical closure after ASD diagnosis and those who did not. METHODS: Using the Korean National Health Insurance Service database, we identified patients with isolated ASDs diagnosed between 1 January 2003 and 31 December 2006. The ASD patients who underwent closure surgery within 6 months after diagnosis were allocated to the early-closure group and the rest were allocated to the conservative-strategy group. The primary outcome was all-cause mortality. Secondary outcomes were atrial flutter/fibrillation (AFF) and ischaemic stroke. RESULTS: Among patients without a history of AFF or stroke, 1644 patients in the early-closure group were propensity score matched to 1644 patients in the conservative-strategy group and their median follow-up durations were 12.9 and 12.8 years, respectively. The early closure was associated with a significantly lower risk of mortality (hazard ratio, 0.55 [95% confidence interval, 0.43–0.70]). In an age-stratified analysis, significant mortality reductions in the early-closure group were found in patients aged 40 years or older. The risk of AFF was significantly higher in the early-closure group, which might be mainly ascribed to postoperative transient AFF, while there was no difference in ischaemic stroke between the 2 groups. CONCLUSIONS: Our data suggest that timely ASD closure without delay is necessary for ASD patients without previous history of clinical events, especially in patients aged 40 years or older. Abstract : Atrial septal defect (ASD) is the third most common type of congenital heart disease, with an estimated incidence of 56 per 100 000 live births [1].